Identidad cultural y la conciencia turística en la Comunidad Nativa de los Boras de San Andrés – Río Momón, 2023 - Garcia Vargas, Vivian Xiomara (2024)
The research work has an objective of determining the relationship between cultural identity and tourist awareness in the Native Community of Boras de San Andrés – Río Momón, 2023, in which an applied type study was used, descriptive-correlational level with a non-experimental design, opting for a population of 120 heads of family, to whom a questionnaire of questions was used to collect information. According to the results obtained, the level of cultural identity is medium (32%), since the person sometimes feels proud of their ethnic group and knows the role it plays in their life, in addition to participating in activities to promote their traditions. . Regarding the level of tourist awareness, it is medium (30%), since sometimes there is friendly treatment to tourists and the tourist resources of the region are promoted. They also occasionally participate in conservation actions and apply knowledge of environmental care. Therefore, a strong positive correlation is determined between cultural identity and tourist awareness, corroborated by Spearman's coefficient of 0.818 and a bilateral sig of 0.000 being statistically significant.